PROMOTION OF PRE-SCHOOLER INTELLECTUAL AND WRITING SKILLS WITH DRAWING ACTIVITIES - Randoha, Antra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
During the pre-school years, development of balance among intellect, emotions and will is of a great significance. Features forming in child – communication skills and abilities, self-esteem, and speech – cannot develop without intellectual progress. Child, yet not knowing intellect, is willing to be active, study and research, i.e., to challenge own mind, and that takes place trough activities engaging body, objects and physical activities. Psychomotor maturity is one of the indicators of pre-schooler’s development; at this age this phenomenon requires specific attention. It is precondition essential for acquisition of drawing and literacy skills – knowledge irreplaceable when accessing basic education. Drawing facilitates intellectual, emotional, and physical development of child (cognition, feelings, perception, thinking, imagination, will, and emotions).